Manfaat Kegiatan Pramuka Dalam Pembentukan Generasi Muda Yang Berkarakter - Lestari, Widya Dwi (Maliki Interdisciplinary Journal, 2024)
Scouting activities play an important role in character development for the youth in Indonesia. Through various outdoor-oriented activities, Scouting educates participants to embody values such as discipline, responsibility, cooperation, and leadership. This research aims to identify the benefits of Scouting activities in the character development of young people. The method used is qualitative analysis, gathering data from interviews, observations, and literature studies. The results indicate that Scouting activities not only enhance practical skills but also foster positive attitudes that support participants’ personal growth. Therefore, Scouting activities can be an effective alternative in educating the youth to become character-driven individuals ready to face future challenges.